Primary Causes for Tooth Extraction Among Patients Attending The IIUM Kulliyyah Of Dentistry Polyclinic - Muhammad Ali, Suhaila; Shaaban Mustafa, Nazih; Ali Kashmoola, Muhannad (IIUM Medical Journal Malaysia, 2017)
Introduction: To investigate the pattern and major causes of tooth extraction among patients attending IIUM Kulliyyah of Dentistry Polyclinic. Materials and Methods: This is a retrospective study. Total 1036 number of tooth extraction done in the polyclinic were recorded to determine the causes of tooth extraction among patients attending the Polyclinic IIUM. Study period was from year 2012 to 2015. Collecting patients’ information was required from Pearl dental system and clinical year students’ Oral Surgery Department logbooks. Information includes patient’s name, identity card number, diagnosis and indications for dental extractions noted for each case. Other demographic features such as age, gender and race were analysed by using SPSS Chi-Square test. Result: The major causes of tooth extraction were dental caries 53.3%, periodontal problem 20.9%, impaction 7.7%, orthodontic reason 4.6%, malposted 3.6%, pre-prosthetic 0.9% and other reasons 8.9%. Among races, Malay had highest tooth extraction cases which were 85.2%, followed by Chinese 11.2%, Indian 2.8% and others 0.8%. Based on gender, female had total of 56.6% of tooth extraction while male 43.4%. Highest prevalence of extraction was patients’ age between 21 to 40 years old (44.4%) followed by age between 41 to 60 years old (35.5%). Conclusion: Dental caries is the major causes for tooth extraction among patients attending IIUM Kulliyyah of Dentistry Polyclinic.